Democracia y sus laberintos - EMMERICH, Norberto; FERNANDEZ, Marta; GARCIA VILA, Gonzalo; ISOARDI, María E.; KERZ, Mercedes; LA RUFFA, Néstor; LEGNANI, Néstor R. (LIBROS DE TIERRA FIRME, 2003)
Otros colaboradores: LEIRAS, Santiago; LOISI, Carlos; MENENDEZ, María C.; MEZA, Sergio; PASTORE, María; POMPOSO, Hugo; RIGOU, Marta; RODRIGUEZ MEDINA, Leandro